Single Cell Protein Production from Lignocellulosic Biomass - Bajpai, Pratima; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on bioconversion of lignocellulosic residues into single-cell protein, which offers an alternative to conventional proteins (such as soybean meal, egg protein or meat protein in animal feed) that is not affected by the climate. It provides an overview of the general uses of lignocellulosic residues and their bioconversion into single-cell protein using microorganisms, as well as the recovery of the valuable by-products. It also explores the benefits and potential drawbacks of single-cell protein, with an emphasis on the economic advantages of such processes. Given its multidisciplinary scope, the book represents a valuable resource for academics and industry practitioners interested in the production of single-cell protein from lignocellulosic residues.
Background -- General Considerations on the Use of Lignocellulosic Residues -- Bioconversion of Lignocellulosic Residues in to Single Cell Protein -- Microorganisms Used for Single Cell Protein Production -- Cultivation of Microorganisms for Single Cell Protein Production.
Keywords: Biotechnology; Green chemistry; Environmental engineering; Bioremediation; Cogeneration of electric power and heat; Fossil fuels; Chemical Bioengineering; Green Chemistry; Environmental Engineering/Biotechnology.; Fossil Fuel